2018
DOI: 10.1093/hmg/ddy046
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of FUS through its low-complexity domain contributes to neurodegeneration

Abstract: Aggregation of fused in sarcoma (FUS) protein, and mutations in FUS gene, are causative to a range of neurodegenerative disorders including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia. To gain insights into the molecular mechanism whereby FUS causes neurodegeneration, we generated transgenic Drosophila melanogaster overexpressing human FUS in the photoreceptor neurons, which exhibited mild retinal degeneration. Expression of familial ALS-mutant FUS aggravated the degeneration, which was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…To verify if BiFC can be used to study the process of aggregate formation in zebrafish, we expressed both TDP-43 and Fus BiFC fusion proteins transiently in zebrafish embryos. Our study revealed fluorescence complementation of wild-type TDP-43 and wild-type Fus and the development of intra-nuclear aggregates, whilst mutant Fus BiFC fusion proteins demonstrated fluorescence complementation in cytoplasmic aggregates as previously reported in cell culture BiFC experiments [75],[77]. Interestingly, co-expression of wild-type and mutant Fus BiFC fusion proteins resulted in fluorescence complementation in intra-nuclear aggregates, not cytoplasmic aggregates, contrary to previously reported findings from cell culture studies and post-mortem tissue [77],[78].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…To verify if BiFC can be used to study the process of aggregate formation in zebrafish, we expressed both TDP-43 and Fus BiFC fusion proteins transiently in zebrafish embryos. Our study revealed fluorescence complementation of wild-type TDP-43 and wild-type Fus and the development of intra-nuclear aggregates, whilst mutant Fus BiFC fusion proteins demonstrated fluorescence complementation in cytoplasmic aggregates as previously reported in cell culture BiFC experiments [75],[77]. Interestingly, co-expression of wild-type and mutant Fus BiFC fusion proteins resulted in fluorescence complementation in intra-nuclear aggregates, not cytoplasmic aggregates, contrary to previously reported findings from cell culture studies and post-mortem tissue [77],[78].…”
Section: Discussionsupporting
confidence: 87%
“…Our study revealed fluorescence complementation of wild-type TDP-43 and wild-type Fus and the development of intra-nuclear aggregates, whilst mutant Fus BiFC fusion proteins demonstrated fluorescence complementation in cytoplasmic aggregates as previously reported in cell culture BiFC experiments [75],[77]. Interestingly, co-expression of wild-type and mutant Fus BiFC fusion proteins resulted in fluorescence complementation in intra-nuclear aggregates, not cytoplasmic aggregates, contrary to previously reported findings from cell culture studies and post-mortem tissue [77],[78]. However, the Matsumoto et al cell culture study did not use a BiFC approach and one possibility is that the intra-nuclear aggregation could represent an early phenomenon (nuclear maturation of the protein followed by cytoplasmic shuttling) that is too late to observe in post-mortem tissue or cell culture models.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…FUS is physiologically involved in RNA metabolism and DNA repair, and there are indications that DNA damage is apparent in FUS-ALS. FUS is normally shuttled between the nucleus and cytoplasm, mainly in the nucleus, and nuclear transport is impaired in patients with FUS-ALS, resulting in mislocalization of FUS in the cytoplasm, self-assembly in the cytoplasm and subsequent neurodegeneration and FUS aggregate formation (Matsumoto et al 2018;De Santis et al 2017). FUS aggregates promote the secretion of tumor necrosis factor-Alpha (TNFα) and thus alter the expression level of AMPA receptors (which mediates glutamate excitatory overexpression), making motoneurons more sensitive to stimuli and leading to excitotoxic damage and cell death, the AMPA-mediated excitotoxic component pathway serves as a potential therapeutic target for FUS-ALS (Kia et al 2018).…”
Section: Fus (Fused In Sarcoma Protein)mentioning
confidence: 99%
“…Provocation of the indeterminate accumulation of multiple protein molecular species characterize essential attributes of a neurodegenerative cascade in terms of accumulated biophysical dimensions for further driven protein unfolding and misfolding. Aggregation of fused in sarcoma (FUS) protein and mutated FUS gene induce neurodegeneration that includes amyotrophic lateral sclerosis and frontotemporal dementia [11]. Nicotinamide function includes the general maintenance of cellular energy levels and the more specific inhibition of nicotinamide adenine dinucleotide-dependent deacetylase sirtuin 1 [12].…”
Section: Linkage Dynamicsmentioning
confidence: 99%